Evaluating the Normative and Structural Explanations of Democratic Peace Theory - Yunizar Adiputera (Institute of International Studies, 2014)
Originating from the work of Immanuel Kant, Democratic Peace Theory proposes that democracies rarely, if ever, fight war against other democracies. While inquiries to the existence of such phenomena through sophisticated statistical approach remain important, it is equally important to further develop the understanding in the causal explanations behind it. There are two dominant strands of explanations for Democratic Peace, one locates the causes on the structure of democratic government, and the other locates them on the prevailing norms/cultures within a democratic society. The structural explanations claim that it is the institutions within democratic governments, such as the presence of regular election, checks and balances (from parliament), and transparency that hinder their leaders to initiate wars against other democracies. The norm/cultural explanations argue that democracies develop liberal ideology, norms of bounded competition, and reciprocity, which guide them in conducting peaceful foreign relations with other democracies. Despite the compelling logics brought by these two types of explanations, there remains a gap between their theoretical assumptions and practical realities of inter-state relations. Furthermore, some of these explanations need to be further specified in order to allow for more operational investigations to them.